A general‐purpose task execution framework for manipulation mission of the 2017 Mohamed Bin Zayed International Robotics Challenge. Issue 1 (31st October 2018) - Hong, Jun; Jung, Seokwoo; Jung, Chanyoung; Jung, Jiwon; Shim, David Hyunchul
Abstract: This paper presents the hardware and software of our team's EurecarBot for Challenge 2 in the 2017 Mohamed Bin Zayed International Robotics Challenge (MBZIRC). Fully automating our robots actions in a real environment required many component technologies for manipulation and vision processing. To perform the complex robotic missions, we developed a task execution framework, which provides a high‐level interface to specify the given tasks. In this study, we focus on the valve operation problem, which was the hardest part of the competition. We also discuss how we overcame the various problems caused by differences between the experimental and the actual competition environments. EurecarBot completed the valve operation mission perfectly in the MBZIRC Grand Challenge and ranked fourth in Challenge 2 and fifth in the Grand Challenge.